A revised and updated checklist of the lizards of Peninsular Malaysia - Grismer, L. Lee (Zootaxa, 2008)
A revised and updated checklist of the lizard fauna of Peninsular Malaysia includes 17 species not present in the most recent checklist (Das & Norsham 2007). Ten of these 17 species were omitted due to apparent oversight and seven others are additions based on subsequent descriptions. An updated taxonomy is employed for the lizard fauna that also alters the species content, bringing the total number of species currently recognized in Peninsular Malaysia from 95 to 108.